Evaluating clinical opinions on the efficacy and tolerability of a novel human milk oligosaccharide-based human milk fortifier containing lactoferrin, docosahexaenoic acid and arachidonic acid - Wazir, Sanjay; Gupta, Shelly (International Journal of Contemporary Pediatrics, 2024)
Background: To gather and analyse the opinions of healthcare professionals regarding the effectiveness and tolerability of a novel human milk oligosaccharide (HMO)-based fortifier containing lactoferrin, docosahexaenoic acid (DHA) and arachidonic acid (ARA) in neonatal nutrition. Methods: A cross-sectional survey was conducted among neonatologists and paediatricians who have utilised the novel HMO-based human milk fortifier (HMoF) in their clinical practice. Participants were asked to provide their feedback on various parameters including nutritional adequacy, growth outcomes, tolerance, and overall clinical efficacy. Results: Majority of respondents reported positive outcomes in terms of enhanced growth parameters, improved gastrointestinal tolerance, and overall health of the infants. The fortifier was particularly noted for its role in supporting the overall growth of the infants including weight gain, length gain and head circumference gain due to the presence of HMOs, lactoferrin, DHA, and ARA. Conclusions: The novel HMO-based human milk fortifier containing lactoferrin, DHA, and ARA has garnered a favourable and positive opinion by healthcare professionals and demonstrates potential benefits in enhancing neonatal nutrition and health outcomes.